Simulation of development dynamics for management improvement of enterprise specialization - Власенко, Тетяна Володимирівна; Власовець, Віталій Михайлович (Technology audit and production reserves, 2016)
Using of the data analysis results of the enterprise development dynamics for management improvement of its specialization allows to prove an influence of the main factors and to set their optimal level for maximum efficiency. A limited set of data and usually functional relationship between them are typical for dynamics data of individual factors characteristic of real enterprises. This leads to significant errors in predicting performance indicators using traditional methods of research. This article is first established the feasibility of the method of statistical equations of dependencies in simulation of development dynamics to improve the management of agricultural enterprise specialization. Effective indicators of economic and financial activities with appropriate focus on best value of formed factors (the maximum for the stimulant performance – yield and minimum for antistimulant performances – harvested area and manufacturing cost) are found. It is established that for an increase in growing profitability of 10 % it is necessary to lay the slowdown of such factors as the production cost at 4,11 % and reduce harvested area at 7,96 %. At the same time it is necessary to intensify the impact of yield at 7,60 %. An increase in productivity of 25 hundred kilograms per hectare will increase profitability in 2,31 times compared to the previous year. Conducted research identifies the main technological reserve of production – ensuring optimal yield of 20,28 hundred kilograms per hectare, which will maximize profitability to 31,19 %. The research results can be used by experts to developing models of management processes.